Microencapsulated macrophages releases conditioned medium able to prevent epithelial to mesenchymal transition - Anna Sola; Laura Saenz del Burgo; Jesús Ciriza; Rosa Maria Hernandez; Gorka Orive; Jorge Martin Cordero; Priscila Calle; Jose Luis Pedraz; Georgina Hotter (Taylor & Francis Group, 2018)
Epithelial to mesenchymal transition (EMT) has emerged as a key process in the development of renal fibrosis. In fact, EMT-derived fibroblasts contribute to the progression of chronic renal disease. In addition, anti-inflammatory M2 macrophages have exhibited a great influence on renal fibrosis. However, because of the high impact that the inputs of different environmental cytokines have on their phenotype, macrophages can easily lose this property. We aim to known if microencapsulated macrophages on M2-inducing alginate matrices could preserve macrophage phenotype and thus release factors able to act on epithelial cells to prevent the epithelial differentiation towards mesenchymal cells. We reproduced an in vitro model of EMT by treating adipose-derived stem cells with all-trans retinoic acid (ATRA) and induced their transformation toward epithelia. Dedifferentiation of epithelial cells into a mesenchymal phenotype occurred when ATRA was retired, thus simulating EMT. Results indicate that induction of M2 phenotype by IL-10 addition in the alginate matrix produces anti-inflammatory cytokines and increases the metabolic activity and the viability of the encapsulated macrophages. The released conditioned medium modulates EMT and maintains healthy epithelial phenotype. This could be used for in vivo cell transplantation, or alternatively as an external releaser able to prevent epithelial to mesenchymal transformation for future anti-fibrotic therapies.